Autosomal dominant TUBB3-related syndrome: Fetal, radiologic, clinical and morphological features. (May 2020) - Blumkin, Lubov; Leibovitz, Zvi; Krajden-Haratz, Karina; Arad, Ayala; Yosovich, Keren; Gindes, Liat; Zerem, Ayelet; Ben-Sira, Liat; Lev, Dorit; Nissenkorn, Andrea; Kidron, Dvora; Dobyns, William B.; et al.
Abstract: Objective: To describe fetal, clinical, radiological, morphological features of TUBB3 related syndrome . Methods: We report two families each of two generations harboring a novel and a previously described heterozygous TUBB3 pathogenic variants. We compared these patients with other published TUBB3 -related cases. We describe the pathological features of dysgyria in the two aborted fetuses. Results: The mother and son from family 1 had a history of mild developmental delay in motor and language skills and demonstrated mild cerebellar signs and mirror movements. Neuroimaging findings included: hypoplastic corpus callosum (CC), asymmetric ventriculomegaly and cerebellar vermis hypoplasia in all patients and frontal dysgyria in three. Autopsy of the fetal brain showed an unusual shape and orientation of the frontal sulci and gyri with normal cortical layering and no abnormal cell types. The mother of family 2 had congenital strabismus, mild muscle weakness on the right and a past history of developmental delay. Fetal brain MRI showed abnormal cerebral sulcation, hemispheric asymmetry, asymmetric ventriculomegaly, dysmorphic short CC and frontal cortical interdigitation. Autopsy demonstrated fronto-parietal predominant dysgyria, bilateral ventriculomegaly, hippocampal and CC hypoplasia, abnormal Sylvian fissure. Lamination and neuron morphology in the areas of dysgyria were normal. Conclusions: TUBB3 related cortical malformations can be mild, consistent with dysgyria rather than typical pachygyria or polymicrogyria. The autopsy findings in fetal TUBB3 related dysgyria are abnormal orientation of sulci and gyri, but normal neuron morphology and layering. We suggest that TUBB3 – associated brain malformations can be suspected in-utero which in turn can aid in prognostic counselling and interpretation of genetic testing. Highlights: We report clinical, radiological and morphological features of TUBB3 related syndrome. We describe for the first time the pathological features of dysgyria. We define "tubulin associated dysgyrias" as a gyral irregularity and sulcal misorientation with normal cortical layering. TUBB3 related cortical malformations can be mild, consistent with dysgyria rather than typical pachygyria or polymicrogyria.